Qualidade fisiológica de sementes de soja em função do pré- resfriamento e do ambiente de armazenamento - Luccas, Anna Carla Souza (2015)
The main challenge of storing soybeans for a certain period of time is to conserve the most of its initial physiological feature. The storage for long periods without temperature and humidity control undermines germination and vigor due to the elevated process of deterioration. Therefore, alternatives for proper storage of high physiological potential seeds are being pursued. In this sense, with the appearance of seed cooling technologies before bagging and during storage, the objective of this study was to investigate the possible reactions of the seeds after dynamic artificial cooling (before bagging), which were stored both at room temperature and under controlled temperature to assess the seeds conditions. Four lots of the cultivar NA 7337 RR with sieves of 5.5 mm and 6.5 mm, cooled to 12°C and 13°C by dynamic process before bagging were used. Seed samples were collected after 0, 45, 90, 135, 180 days of storage in two different environments: common warehouse (without temperature control) and refrigerated warehouse (with temperature control). The seeds were submitted to evaluated parameters: germination, accelerated aging, seedling emergence in sand, germination speed index, electrical conductivity, tetrazolium, weight of 1000 seeds, humidity and computerized image analysis. It was concluded that the dynamic artificial pre-cooling before bagging is important in the conservation of soybean seed quality, but it must be associated to a storage room with controlled temperature and humidity.